The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1071/ar03104
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Brassica break-crops on soil biology and yield of following wheat crops

Abstract: Biofumigation refers to the allelopathic effects of brassicas on non-desirable soil organisms in a rotation cropping system. These effects are additional to non-hosting of root diseases, responsible for much of the break-crop effect observed in a following cereal crop. We investigated the biofumigation impacts of canola on take-all disease and rhizosphere microorganisms of following wheat crops. The biofumigation potential of the canola was tested by comparing effects of Brassica and non-Brassica break-crops a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…(18,31). Smith et al (32) failed to observe changes in microbial communities by Brassica tissues when the following crop was wheat. In in vitro studies (28,32), Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…(18,31). Smith et al (32) failed to observe changes in microbial communities by Brassica tissues when the following crop was wheat. In in vitro studies (28,32), Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies revealed that such suppression was often not evident as disease reductions in following crops (Smith et al 2004), partly due to the relatively low concentrations of 2PE-ITC (*1 nmol g -1 soil) which have been measured in the rhizosphere of growing plants Marschner 2003, 2004). An example is the reported increase in levels of the biocontrol fungus Trichoderma spp.…”
Section: Use Of Gsl In Agriculture: Biofumigationmentioning
confidence: 99%
“…However, the available evidence suggests that the benefit of a rape break-crop in a wheat rotation results largely from the non-hosting of takeall (Gaeumannomyces graminis var. tritici) rather than any biofumigation (Smith et al 2004). Thus, choice of breakcrop should be made on agronomic characteristics and soil structural benefits rather than potential biofumigation effects.…”
Section: Choice Of Cropmentioning
confidence: 99%